Understanding of Public Relation Officer towards Transparency and Accountability of Information in Online Public Relation Implementation in Public Institutions - Azhary, Syaiful; Kriyantono, Rachmat (Jurnal Pekommas, 2018)
This research with mixed research methods aims to explore the understanding of government public relations on information transparency and accountability in implementing online public relations. Qualitative data is obtained through in-depth interviews with public agency website managers. Qualitative methods are used to obtain data regarding the perception of website managers on the functions and features of the official website of the public agency they manage. The qualitative method is used to obtain an overview of how the government public relations understanding on the transparency and accountability of information in their online PR applications is contained in the systematic features and contents of their agency's website. In addition, this method is also to find out the constraints faced by public relations public agencies in building and managing their online PR.It resulted in the finding that online public relations of public agencies in Indonesia have not been ideal in embedding transparency, interactivity, usability, and maturity websites on their websites. In addition, this study also found that the operationalization of interactivity became the dominant element in activities on the official social media platforms of public bodies in Indonesia. They use social media more than official websites, so researchers argue that understanding of the public relations on information transparency and accountability is lacking.